Epilepsy due to Intracranial Surgery: 15 Years of Experience - Gönül AKDAĞ; Demet İLHAN ALGIN; Ahmet MUSMUL; Oğuz Osman ERDİNÇ (Archives of Epilepsy, 2017)

(untitled)
Objectives:Epidemiological studies have shown increased incidence of epilepsy in cases of brain trauma, central nervous system infection, cerebrovascular disease (CVD), and brain tumours. The etiology of epilepsy vary by age of the patient. In the etiology of partial and secondarily generalized partial seizures in adult patients, CVD is the most common cause of acute, symptomatic seizures. Frequency of seizures is estimated to be 15% to 20% after cranial operation.Methods:Eighty-four patients who were admitted to epilepsy clinic between 2000 and 2015 with history of cranial surgery and symptomatic seizures were included in the present study.Results:Etiology conditions were 41 (48.8%) cases of space-occupying lesions (SOL), 19 (22.6%) instances of trauma, 19 (22.6%) cases of CVD, and 5 (6.0%) with ventriculoperitoneal shunt. Preoperative seizures had been observed in 17 (20.2%) of patients. No seizure was seen in 11 (13.1%) patients. Electroencephalography findings revealed focal abnormalities in 39 (46.4%) patients, and were normal in 26 (31.0%) patients. Total of 43 (51.2%) patients were treated with monotherapy, and 32 (38.1%) patients were under polytherapy.Conclusion:Most common etiological factor for patients with pre- or postoperative epilepsy who had undergone cranial surgery was SOL. Focal EEG results commonly indicate lesions. Onset of seizures may be delayed. Patients responded well to monotherapy treatment of seizures.